Prevalence, risk factors, and parental perspectives of dental caries in children in Odisha: A mixed-method study - Smrutirekha Mohanty; Deepanjali Behera; Snehasish Tripathy; Madhusmita Jena; Manas Ranjan Behera; Bhuputra Panda (Elsevier, 2024)
Background/objective: Despite numerous advances in dentistry, the frequency of dental caries remains high, especially among children. Therefore, the study's objectives were to assess the prevalence of dental caries in school-aged children between ages 6-14 years, to identify the risk factors associated with dental caries and to explore parents' understanding and awareness of preventing dental caries among children. Method: A mixed method study was conducted in the rural areas of Cuttack and Jagatsinghpur districts in Odisha, India. Children were chosen from schools using a multistage sampling process. Pretested and standardised questionnaires were utilized to collect data from children, while interviews with parents and teachers were employed to collect qualitative data. The DMFT/DEFT index was calculated for children. Data were analysed using frequency, percentage and binary multiple logistic regression analysis. The interviews were analysed using thematic analysis. Result: A total of 419 children, 14 parents, and 12 teachers participated in the study. The findings of the current study reported the prevalence of dental caries in 60 % of children. In addition, age, a high frequency of sugar and chocolate consumption, and poor socioeconomic status were found to be associated with a high risk of dental caries. Furthermore, the results of the thematic analysis indicated parent and teacher awareness and understanding of dental caries; however, it highlights the need for improved oral health practices. Conclusion: These insights from qualitative and quantitative findings can guide the development and improvement of preventive interventions to combat dental caries through implementing oral health programs in schools, thereby fostering better oral health and overall well-being among the younger population.